DEVELOPMENT AND IMPACT OF BUSINESS INTELLIGENCE SYSTEMS (BIS) IN RETAIL DECISION-MAKING PROCESSES: A SYSTEMATIC REVIEW - CASTAÑEDA HILARIO, ARADIEL (2024)
THIS ARTICLE ADDRESSES THE APPLICATION OF BUSINESS INTELLIGENCE AND THE USE OF TECHNIQUES AND TOOLS IN BUSINESS ENVIRONMENTS AND HOW IT HAS SIGNIFICANTLY IMPROVED THE DECISION MAKING THAT IS CARRIED OUT IN ALL BUSINESS AREAS. HOWEVER, THERE ARE DIFFERENCES AND THERE IS A GAP BETWEEN THE APPLICATION OF THIS CONCEPT AT THE NATIONAL LEVEL AND AT THE INTERNATIONAL LEVEL. THIS ARTICLE ADDRESSES THE MAIN ACHIEVEMENTS AND RESULTS OBTAINED BY RESEARCH APPLIED TO BUSINESS INTELLIGENCE AT BOTH LEVELSF MENTIONED, HIGHLIGHTING THEIR PROCEDURES, METRICS, TOOLS AND RELIABILITY METHODS. 17 ARTICLES WERE IDENTIFIED BETWEEN THE YEARS 2016 AND 2023 USING THE PRISMA METHODOLOGY. THESE ARTICLES UNDERWENT A SYSTEMATIC REVIEW THAT ALLOWED US TO IDENTIFY EXISTING GAPS AND PROVIDE OPPORTUNITIES FOR IMPROVEMENT ACCORDING TO THE RESULTS OBTAINED. © 2024 LATIN AMERICAN AND CARIBBEAN CONSORTIUM OF ENGINEERING INSTITUTIONS. ALL RIGHTS RESERVED.